Lecythidaceae Poit. in the Tupé sustainable development reserve, Manaus, Brazil - Matta, Luisa Brasil Viana; Scudeller, Veridiana Vizoni (Revista Brasileira de Botanica, 2012)
Lecythidaceae is the family of the Brazil nut, and comprises about 300 species belonging to 17 genera with pantropical distributions. One hundred and twenty-two species belonging to nine genera are distributed throughout Brazil, demonstrating its greatest diversity in the Amazon rainforest where Lecythidaceae is also one of the most abundant families. It is usually difficult to collect fertile material from these trees because of their canopy heights, and species determinations using sterile material can be complex because of their morphological similarities. There have been relatively few studies of this family even though it is one of the most important groups in the Amazon region, and a detailed taxonomic treatment of the species of Lecythidaceae in the Tupé Sustainable Development Reserve was therefore the goal of the present work. Ten species were found, Allantoma lineata (Mart. ex O.Berg) Miers, Bertholletia excelsa Bonpl., Couratari tenuicarpa A.C.Sm., Lecythis poiteaui O.Berg; and six species of Eschweilera, the richest genus. The descriptions and identification keys of the species used 56 characters. The main reproductive characters useful for distinguishing the species were the pubescence of the inflorescence rachis, pedicel length and trichomes presence, floral symmetry, hood type, filament shape, stigma shape, fruit shape and size, and aril type. The most diagnostic vegetative characters were the type and color of the outer bark, inner bark color, midrib prominence, and petiole shape and pubescence.
Keywords: Allantoma Lineata; Bertholletia Excelsa; Couratari; Eschweilera; Lecythidaceae; Lecythis